Health professionals: facilities and difficulties encountered during notification, family approach and organ procurement (Research, Society and Development, 2020)
Objective: to identify the facilities and difficulties encountered by health professionals of an Intra-Hospital Committee for Donation of Organs and Tissues for Transplants from a Hospital Institution in Southern Brazil during the notification process, family approach and organ procurement for transplants. Method: qualitative research, through an interview with 20 workers of an Intra-Hospital Committee for Donation of Organs and Tissues for Transplants, applying the technique of Discursive Textual Analysis. Results: two categories emerged: facilitating aspects for health professionals in the notification process, family approach and organ procurement and difficulties encountered by health professionals during the notification process, family approach and organ procurement. Conclusion: the results suggest the importance of implementing strategies with the objective of attributing more social value to the donation, with greater awareness of the population and health professionals better trained to efficiently coordinate the process.